5G empowers digital transformation of industries:scenario, pathway and business model - Keqiang GUO; Feng CHENG; Zhenlong TAN (Dianxin kexue)
Accelerating digital transformation is an inevitable choice of responding to the call-up of the government, conforming to economic laws and promoting enterprise-self development.5G is the core of the new generation of information and communication technologies, and therefore is the key to the digital transformation of the enabling industry.Telecom operators have carried out 5G application pilot projects with vertical industries.While there are many problems in the application division system of segmented industries proposed by clustering, and the development path and business model of integration are still unclear.To this end, by using two dimensions based on vertical industry and application services, the new system of application scenarios of 5G+industries was presented, and three kinds of 5G+industries convergence development path and mode were presented: the first is a supplement, substitution or upgrade to the original networks for vertical industry, the second is using 5G as the contact and carrier service of computing resource, and the last is to promote industrial ecology fusion profoundly.